Characterization of Diarreaghenic Escherichia coli Strains Isolated from Healthy Donors, including a Triple Hybrid Strain - Evelyn Méndez-Moreno; Liliana Caporal-Hernandez; Pablo A. Mendez-Pfeiffer; Yessica Enciso-Martinez; Rafael De la Rosa López; Dora Valencia; Margarita M. P. Arenas-Hernández; Manuel G. Ballesteros-Monrreal; Edwin Barrios-Villa (MDPI AG, 2022)
Escherichia coli is a well-recognized inhabitant of the animal and human gut. Its presence represents an essential component of the microbiome. There are six pathogenic variants of E. coli associated with diarrheal processes, known as pathotypes. These harbor genetic determinants that allow them to be classified as such. In this work, we report the presence of diarrheagenic pathotypes of E. coli strains isolated from healthy donors. Ninety E. coli strains were analyzed, of which forty-six (51%) harbored virulence markers specifics for diarrheagenic pathotypes, including four hybrids (one of them with genetic determinants of three DEC pathotypes). We also identified phylogenetic groups with a higher prevalence of B2 (45.6%) and A (17.8%). In addition, resistance to sulfonamides (100%), and aminoglycosides (100%) was found in 100% of the strains, with a lower prevalence of resistance to cefotaxime (13.3%), ceftriaxone (12.2%), fosfomycin (10%), and meropenem (0%). All analyzed strains were classified as multidrug resistant. Virulence genes were also investigated, which led us to propose three new virotypes. Among the virulence traits observed, the ability to form biofilms stands out, which was superior to that of the E. coli and Staphylococcus aureus strains used as positive controls.